2015
DOI: 10.1007/s10712-015-9333-3
|View full text |Cite
|
Sign up to set email alerts
|

3D Attenuation Tomography of the Volcanic Island of Tenerife (Canary Islands)

Abstract: This paper shows a new multidisciplinary interpretation approach to the internal structure of Tenerife Island. The central core of this work is the determination of the three-dimensional attenuation structure of the region using P-waves and the coda normalization method. This study has been performed using 45,303 seismograms recorded at 85 seismic stations from an active experiment (air gun shots) conducted in January 2007. The interpretation of these new results is done combining the new images with previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 68 publications
5
28
0
Order By: Relevance
“…A similar high‐frequency, low‐attenuation anomaly marks the location of the deep magma conduits feeding Mount St. Helens volcano [ De Siena et al , ]. Seismic attenuation tomography using coda‐normalized direct energies at Tenerife Island reveals that low‐attenuation anomalies are related to the position of potential ancient magma reservoirs [ Prudencio et al , ]. As shown by Di Vito et al [] using the historical, archeological, and geological record of Campi Flegrei caldera, progressive magma accumulation has been acting under the caldera center in a 4.6 ± 0.9 km deep source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar high‐frequency, low‐attenuation anomaly marks the location of the deep magma conduits feeding Mount St. Helens volcano [ De Siena et al , ]. Seismic attenuation tomography using coda‐normalized direct energies at Tenerife Island reveals that low‐attenuation anomalies are related to the position of potential ancient magma reservoirs [ Prudencio et al , ]. As shown by Di Vito et al [] using the historical, archeological, and geological record of Campi Flegrei caldera, progressive magma accumulation has been acting under the caldera center in a 4.6 ± 0.9 km deep source.…”
Section: Resultsmentioning
confidence: 99%
“…The objective is to locate and model in space the sources of high fumarolic activity, ground deformation, and hydrothermal activity during the unrest [Todesco et al, 2010;Chiodini et al, 2010;Amoruso et al, 2014a]. The increased lateral illumination with respect to standard Q c imaging may lead to better understanding of the feeding mechanisms active at the volcano at present and historical times [Todesco et al, 2014;Di Napoli et al, 2016;Di Vito et al, 2016], as done at other volcanoes [Prudencio et al, 2015a[Prudencio et al, , 2015b. The study thus gives a different seismic imaging perspective on the problem of locating deformation and unrest sources related to hydrothermal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…While scattering imaging does not allow inferring about the current state of these anomalous bodies, which can consist of already solidified intrusions, a receiver function study suggests a low S‐wave velocity zone starting at a depth of about 8 km (Lodge et al, ). Finally, an attenuation tomography study found no evidence of active magma chambers at shallow depth (Prudencio et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As it was mentioned for the existing physical volcanology data, geophysical data have not been considered in any of the works that support an origin of the caldera by sector collapse. However, geophysical studies, including magnetism, gravimetry, magnetotellurics, audio-magnetotellurics, seismic tomography, and self-potential studies, provide structural data on the interior of Tenerife that are crucial to interpret the internal structure of the Las Cañadas caldera and consequently, its origin (see MacFarlane and Ridley, 1968;Vieira et al, 1986;Ortiz et al, 1986;Camacho et al, 1991Camacho et al, , 2011García et al, 1997;Aubert and Kieffer, 1998;Ablay and Kearey, 2000;Araña et al, 2000;Almendros et al, 2000Almendros et al, , 2007Pous et al, 2002;Gottsmann et al, 2008;Coppo et al, 2008Coppo et al, , 2010Garcia-Yeguas, 2010;Blanco-Montenegro et al, 2011; De Barros et al, 2012;García-Yeguas et al, 2012Prudencio et al, 2013Prudencio et al, , 2015Piña-Varas et al, 2014Villasante et al, 2014). Summarising the main findings among all these studies, the following observations arise ( Fig.…”
Section: On-land Geophysicsmentioning
confidence: 99%